Seismic Resilience Evaluation of Reinforced Concrete Frame Considering the Effect of Mainshock-Aftershock Sequences - Peiran Li; Xueqian Li; Xin Wang; Ding Wang (Applied Sciences, 2023)
The effect of aftershocks on the function recovery process of damaged structures after large earthquakes cannot be ignored in the resilience evaluation of buildings and communities. Based on the Monte Carlo simulation method, this paper proposes an approach to evaluate the seismic resilience of reinforced concrete frame considering the effect of mainshock-aftershock sequences. The findings of this study can provide a reference for the seismic performance evaluation of reinforced concrete frame structures under aftershocks.